Effectiveness of Renal Denervation Therapy in Persistent Hypertension: A Meta-Analysis - Mulia, Deddy Primadona; Syahpri Putra Wangsa; Kgs. M. Yusuf Arief Akbar; Edy Nur Rachman; Chairil Makky; Eva Julita; Zulkhair Ali; Novadian Suhaimi; Suprapti Slamet; Ian Effendi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Persistent hypertension is a global health problem that requires effective therapy. Renal denervation (RDN) therapy is emerging as a promising new option. This meta-analysis aims to evaluate the effectiveness of RDN in patients with persistent hypertension. Methods: We performed a systematic search in PubMed, Scopus, and the Cochrane Library for studies evaluating the effectiveness of RDN in patients with persistent hypertension. Data were extracted and analyzed using a random effects model. Results: A total of 12 studies with a total of 1,024 patients were included in this meta-analysis. RDN demonstrated significant reductions in systolic and diastolic blood pressure compared with controls (MD -12.3 mmHg [95% CI -15.8 to -8.8] for systolic blood pressure and MD -6.1 mmHg [95% CI -8.2 to -4.0] for blood pressure diastolic). The effectiveness of RDN is higher in patients with more severe hypertension and in patients who are unresponsive to antihypertensive drugs. Conclusion: RDN is an effective therapy for persistent hypertension, especially in patients with more severe hypertension and in patients who are unresponsive to antihypertensive drugs.